Pancreatic α-cell hyperplasia and hyperglucagonemia due to a glucagon receptor splice mutation. (21st November 2016) - Larger, Etienne; Wewer Albrechtsen, Nicolai J; Hansen, Lars H; Gelling, Richard W; Capeau, Jacqueline; Deacon, Carolyn F; Madsen, Ole D; Yakushiji, Fumiatsu; De Meyts, Pierre; Holst, Jens J; Nishimura, Erica
Summary: Glucagon stimulates hepatic glucose production by activating specific glucagon receptors in the liver, which in turn increase hepatic glycogenolysis as well as gluconeogenesis and ureagenesis from amino acids. Conversely, glucagon secretion is regulated by concentrations of glucose and amino acids. Disruption of glucagon signaling in rodents results in grossly elevated circulating glucagon levels but no hypoglycemia. Here, we describe a patient carrying a homozygous G to A substitution in the invariant AG dinucleotide found in a 3′ mRNA splice junction of the glucagon receptor gene. Loss of the splice site acceptor consensus sequence results in the deletion of 70 nucleotides encoded by exon 9, which introduces a frame shift and an early termination signal in the receptor mRNA sequence. The mutated receptor neither bound 125 I-labeled glucagon nor induced cAMP production upon stimulation with up to 1 µM glucagon. Despite the mutation, the only obvious pathophysiological trait was hyperglucagonemia, hyperaminoacidemia and massive hyperplasia of the pancreatic α-cells assessed by histology. Our case supports the notion of a hepato–pancreatic feedback system, which upon disruption leads to hyperglucagonemia and α-cell hyperplasia, as well as elevated plasma amino acid levels. Together with the glucagon-induced hypoaminoacidemia in glucagonoma patients, our case supports recent suggestions that amino acids may provide the feedback link between the liver and the pancreatic α-cells. Learning points: Loss of function of the glucagon receptor may not necessarily lead to the dysregulation of glucose homeostasis. Loss of function of the glucagon receptor causes hyperaminoacidemia, hyperglucagonemia and α-cell hyperplasia and sometimes other pancreatic abnormalities. A hepato–pancreatic feedback regulation of the α-cells, possibly involving amino acids, may exist in humans.